Comparative Analysis Of Stock Liquiditi Level, Price Share And Stock Returns Before And After Stock Split On The Compass 100 Index Year 2017-2021 - Putri Dewi Permatasari; Agustina Widodo (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study aims to examine differences in stock liquidity, stock prices and stock returns before and after a stock split. This type of research is quantitative research. The objects in this study were companies listed on the Indonesia Stock Exchange (IDX) in the Kompas 100 index category. The sampling technique in this study used purposive sampling. The number of samples is 13 companies. Data collection using documentation techniques. The results of the paired sample t-test showed that there was no difference in stock liquidity before and after the stock split with a significance value of 0.968. There is no difference in stock prices before and after the stock split with a significance value of 0.079. There is a difference in abnormal returns before and after the stock split with a significance value of 0.000.